Anterior cervical decompression and fusion surgery for cervicogenic headache: A multicenter prospective cohort study - Yang, Liang; Li, Yongchao; Dai, Chen; Pang, Xiaodong; Li, Duanming; Wu, Ye; Chen, Xiongsheng; Peng, Baogan (Frontiers in Neurology, 2022)
Background: Cervicogenic headache (CEH) has long been thought to be a referred pain originating from pathological changes in the upper cervical nerves. However, previous clinical studies found that anterior lower cervical discectomy for the treatment of cervical myelopathy and/or radiculopathy also helps to alleviate associated headaches. To date, there is still a lack of large sample and prospective study to investigate the effect of anterior cervical decompression and fusion (ACDF) on CEH associate with cervical spondylosis. Methods: Six hundred and fifty-six patients with cervical radiculopathy and/or myelopathy were enrolled in three spinal centers. Among them, 221 patients who were diagnosed with CEH were collected in this study, and 204 completed one-year follow-up. The primary end point was patient’s headache intensity as measured by the numeric pain rating scale (NPRS) during 12 months of follow-up. Secondary outcome measures included the neck disability index (NDI), headache frequency, and headache duration. Results: Among all 204 CEH patients who completed one-year follow-up, 166 received anterior cervical surgery (surgery group) and 38 received conservative treatment (conservative group). There were statistically significant lower NPRS in the surgical group during follow-up. Between-group differences revealed that the surgery group experienced statistically significant greater improvement in the NPRS at 1-month (2.8, 95 % CI: 2.0, 3.6), 3-month (2.6, 95 % CI: 1.8, 3.4), 6-month (2.4, 95 % CI: 1.6, 3.2) and 12-month (1.5, 95 % CI: 0.7, 2.4) (p < 0.05 for all). There were statistically significant lower NDI, less frequent headaches and lower headache duration in the surgery group during follow-up (p < 0.05 for all). Conclusions: Current study indicates that anterior cervical surgery can effectively relieve CEH associated with cervical spondylosis. Since cervical spondylosis usually occurs in the lower cervical spine, the study suggests that pain afferents from lower cervical nerves may converge to trigeminocervical nucleus.